2022
DOI: 10.1002/pc.27100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel natural cellulosic fibers from Abutilon Indicum for potential reinforcement in polymer composites

Abstract: The prime objective of this research study was the investigation the new natural cellulosic fiber extracted from the stem of Abutilon Indicum plants as an alternative reinforcement in greener composite materials for structural applications. Abutilon Indicum a flowering plant with unique medicinal values are abundantly found in India and other south Asian countries. The fibers extracted from the stem of the Abutilon Indicum plant are proven to be sustainable, ecofriendly, and novel and hence this fiber is chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…The degradation rate of lignin at high temperatures is lower than that of cellulose and hemicellulose; therefore, its resistance to high temperatures is higher than that of cellulose and hemicellulose. The high lignin content of the CBF fiber is thought to provide good thermal stability [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The degradation rate of lignin at high temperatures is lower than that of cellulose and hemicellulose; therefore, its resistance to high temperatures is higher than that of cellulose and hemicellulose. The high lignin content of the CBF fiber is thought to provide good thermal stability [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This section discusses the exploration of thermal stability in novel natural fibres based on various research conducted in recent times. Arun Ramnath et al [70] experimented the thermal analysis on Abutilon indicum fibres and reported that due to wettability of the raw fibre, its degradation is lower. However, for NaOH-treated A. indicum fibres, it shows the better thermal degradation at the range of 335-363 °C.…”
Section: Thermal Characteristicsmentioning
confidence: 99%
“…The findings suggest that alkali treatment removes waxy layers and other impurities on the surface of the fibres, resulting in better thermal stability. Similarly, Divya et al [73] explored the thermal stability of the novel Furcraea selloa and stated that this fibre is more thermally stable (up to 365.8 °C) than A. indicum [70], F. benjamina [71], and PVF [72] due to the presence of secondary metabolites in F. selloa; the fibre is more thermally stable.…”
Section: Thermal Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…ArunRamnath in his research investigations reviewed and experimentally investigated the machining performance of various composite materials for determination of suitable optimization technique and ideal machining parameter combinations with regard to the selection of ideal machining parameters in end milling epoxy granite composites. [42][43][44][45][46][47][48][49][50][51] With a similar research methodology, the results of static, dynamic and thermal characteristics of research investigations of 70 different machine tool structures are identified and summarized and further the design methodologies employed are analyzed with the objective of enhanced performance and functionality of machine tool structures. This review work performed provides a clear ideology on machine tool structures and aids researchers, scientists and metallurgists in development of machine tool structures by epoxy granite composites and other polymer concrete reinforced composites with the objective of minimization of thermal errors without any trade-off among static and dynamic properties.…”
Section: Introduction and Present Scenariomentioning
confidence: 99%